The effect of doxazosin and sildenafil citrate combination on bladder tissue contractility, alpha adrenergic receptor, and iNOS subtype expression in a male rat model of partially bladder outlet obstruction - TİNAY, İLKER; ÖZYÜREK, MUSTAFA; TARCAN, TUFAN; TANIDIR, YILÖREN (WILEY, 2017)
AimsOur aim was to investigate the effects of doxazosin, sildenafil, and their combination on bladder tissue contractility and adrenergic receptor (AR) and inducible nitric oxide synthase (iNOS) expression utilizing a male rat model of partial urethral obstruction (PUO). MethodsThirty male Sprague Dawley rats were divided into five groups. Except the SHAM group, all animals in remaining four groups underwent surgery for PUO. No further treatment was given to the first group (NT group). Remaining three groups received 6 weeks of treatment with 20mg/kg doxazosin (D group), 20mg/kg sildenafil (S group), 20mg/kg doxazosin, and 20mg/kg sildenafil combination (DS group), respectively via oral gavage. Then, bladder strips were harvested from each animal for isometric tension studies and for real time polymerase chain reaction studies of both AR subtypes and iNOS mRNA. ResultsContractile responses to carbachol and electrical field stimulation at various concentrations/frequencies showed a significant increase after PUO. Any treatment helped to normalize these increased responses. Alpha 1a and 1d AR subtype expressions were found to be down- and up-regulated, respectively, in every group with PUO, compared to SHAM group. iNOS expression was similar in D and NT groups and significantly increased in S and DS groups. ConclusionsContractile changes of rat bladder tissue due to PUO were prevented by sildenafil or doxazosin alone or in combination where combination treatment did not provide any additional advantage. Further studies are needed to clarify the role of phosphodiesterase inhibitors and combination treatment in the treatment of LUTS.
Keywords: bladder outlet obstruction; doxazosin; isometric tension studies; receptors; sildenafil; URINARY-TRACT SYMPTOMS; NITRIC-OXIDE SYNTHASE; BENIGN PROSTATIC HYPERPLASIA; PARTIAL URETHRAL OBSTRUCTION; SMOOTH-MUSCLE-CELLS; ERECTILE DYSFUNCTION; GUANYLYL CYCLASE; MESSENGER-RNA; HUMAN BPH; INHIBITORS